CHILDHOOD OBESITY: A STUDY AMONG TWO SOCIO-ECONOMIC GROUPS OF KOLKATA, WEST BENGAL - Ghosh Roy, Abhishikta; Maity, Madhuparna; Dasgupta, Monimekhala; Ratan Bandyopadhyay, Arup (IJRDO - Journal of Social Science and Humanities Research, 2016)
Obesity is a global health problem at epidemic proportions. The prevalence of childhood overweight and obesity increased during the 1980s to the late 1990s. The prevalence of obesity is higher in socially and economically disadvantaged communities in most Westernised countries. Potential links to childhood overweight and obesity include elevated risk of health concerns. The present study tried to understand the prevalence of obesity among children of contrasting socio-economic groups and its concomitants. A total of 200 participants have been included in the present study, The results show that none of the participants of either socio-economic groups are overweight or obese. Interestingly, less number of participants of HSEG are underweight that LSEG.